Winter diet analysis of leopard (Panthera pardus) in the Nagarjun Forest of Shivapuri Nagarjun National Park - Shrestha, Sandhya; Koju, Narayan Prasad; Thapa Magar, Ashim; Shrestha, Sudhan Bhakta; Ghimire , Shristi (Banko Janakari, 2025)
The leopard (Panthera pardus) is a common and wide-ranged wild cat species listed in the vulnerable category of the IUCN Red List of Threatened Species. It is distributed widely in different protected areas and the human-dominated landscape of Nepal. The current study explored the winter diet of leopard in the Nagarjun Forest, Shivapuri Nagarjun National Park. A total of 16 scat samples of leopards from Nagarjun Forest were opportunistically collected between November and January 2022 and were analyzed for their diet composition based on microhistological analysis. Altogether 13 prey species were identified in the scats, compromising 11 wild and 2 domestic species. The primary wild prey was the wild boar with a percent occurrence of 81.25% and percentage biomass consumption of 30.76%. Among domestic prey was the dog with a percent occurrence of 43.75% and percentage biomass consumption equal to 12.25%. The measurements for length, overall hair diameter, medullar diameter, and medullary index were determined. The findings suggests that the winter diet of leopards of Nagarjun Forest is primarily sustained by wild prey, with smaller contributions from livestock. We suggest further studies on the seasonal dietary composition of this apex predator.